Effectiveness and safety of endosonography-guided liver biopsy in liver disease at a level III public hospital - Li Salvatierra, Bruno (2023)
Parenchymal liver diseases are commonly evaluated by laboratory and imaging studies. However, in some cases a liver biopsy is required. Endoscopic ultrasonography-guided liver biopsy (EUS-LB) has been reported as a procedure with high diagnostic yield (90-100%) with low adverse event profile, but there are not studies which report about the experience and technique in our country. Objective: Determinate the effectiveness and the safety of endosonography-guided liver biopsy in liver parenchymal disease. Materials and methods: A prospective study was conducted at a III-2 level of care Public Hospital in Lima, Peru. It included patients over 18 years of age with suspicion of parenchymal liver disease who underwent EUS-LB for study hepatic parenchymal disease since March of 2018 to October of 2022. Results: The diagnostic yield of the biopsies was 77.02%, with a mean length of the sample of 13.98mm (standard deviation 7.34) and a median of 8 complete portal spaces (0-50). Only 31.25% of the procedures were performed with a fine needle biopsy (FNB), finding a significant difference between the type of needle and the diagnostic yield (p=0.01). The most common histopathological diagnosis was autoinmune hepatitis. There were 2.08% of post-procedure complications. Conclusions: EUS-LB for the diagnosis of liver parenchymal disease had a diagnostic yield close to 80% in our region with a low profile of adverse events. However, more prospectives studies with a larger number of patients are required.